Postharvest treatments of wild pepper (Piper spp.) in Madagascar. (12th September 2014) - Weil, Mathieu; Descroix, Frédéric; Shum Cheong Sing, Alain; Boulanger, Renaud; Hoarau, Mathilde; Levesque, Annaïg; Bohuon, Philippe
Abstract : Introduction . A study on postharvest treatments of wild peppers was carried out in Madagascar with the aim of describing the local practices and measuring their impacts on the quality of the products.Materials and methods . Four distinct pepper production systems (PPS) were observed, described and compared in two separate areas in East Madagascar. Major quality characteristics (piperine and essential oil) of the peppercorns were assessed in samples collected in the four systems.Results and discussion . Two main postharvest processes (dry and wet) were identified. The wet process differed from the dry one in that it involved two specific operations, blanching and sweating. The processes influenced the color of the pepper. Piperine contents were not affected by any of the pepper production systems, whereas essential oil contents were reduced by up to 27% by the wet process. After processing, piperine contents were up to eight times lower, whereas essential oil contents were up to six times higher than the specifications of the standard ISO 959-1 for black pepper ready for commercialization.Conclusion . Two main processes (dry and wet) for treatment of peppercorns in Madagascar were identified and described. The dry process, with two steps less, appeared to be easier to implement and more respectful to the product. Improving maturity control and processing according to the quality expected by the markets will be necessary to promote Malagasy peppers.